Organizing scientific investigations in the Tomsk Medical Institute in the 30th years of XX century - M. V. Gribovsky (Бюллетень сибирской медицины, 2006)
The paper is devoted to the peculiarities of scientific investigation organizing in the Tomsk Medical Institute in the 30th years of XX century. In these years, the Tomsk Medical Institute became self-dependent medical institute of higher education.